A series of BiOxIy/GO photocatalysts: synthesis, characterization, activity, and mechanism. Issue 86 (31st August 2016) - Chou, Shang-Yi; Chung, Wen-Hsin; Chen, Li-Wen; Dai, Yong-Ming; Lin, Wan-Yu; Lin, Jia-Hao; Chen, Chiing-Chang
Abstract : Four composites BiOI/GO, Bi4 O5 I2 /GO, Bi7 O9 I3 /GO, and Bi5 O7 I/GO. Abstract : A series of bismuth oxyiodide (BiO x I y )-grafted graphene oxide (GO) sheets with different GO contents were synthesized through a simple hydrothermal method. This is the first report where four composites of BiOI/GO, Bi4 O5 I2 /GO, Bi7 O9 I3 /GO, and Bi5 O7 I/GO have been characterized using X-ray diffraction, transmission electron microscopy, scanning electron microscopy energy-dispersive spectroscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and diffuse reflectance spectroscopy. The assembled BiO x I y /GO composites exhibited excellent photocatalytic activities in the degradation of crystal violet (CV) under visible light irradiation. The order of rate constants was as follows: Bi7 O9 I3 /GO > Bi4 O5 I2 /GO > Bi4 O5 I2 > Bi7 O9 I3 > Bi5 O7 I/GO > BiOI/GO > BiOI > Bi5 O7 I > GO. The photocatalytic activity of the Bi7 O9 I3 /GO (or Bi4 O5 I2 /GO) composite reached a maximum rate constant of 0.351 (or 0.322) h −1, which was 1.8 (or 1.7) times higher than that of Bi7 O9 I3 (or Bi4 O5 I2 ), 6–7 times higher than that of BiOI/GO, and 119–130 times higher than that of BiOI. The quenching effects of different scavengers and electron paramagnetic resonance demonstrated that the superoxide radical (O2 ˙ − ) played a major role and holes (h + ) and hydroxyl radicals (˙OH) played a minor role as active species in the degradation of crystal violet (CV) and salicylic acid (SA). Possible photodegradation mechanisms are proposed and discussed in this research.